A contribution to the aphid fauna (Homoptera, Aphidinea) of the Republic of Dagestan (the Russian Federation), with descriptions of three new species, redescription of Macrosiphum pulcherimum Nevsky, 1928, and descriptions of previously unknown morphs of three species - Stekolshchikov, Andrey V. (Zootaxa, 2024)
An updated aphid (Homoptera, Aphidinea) check-list of the Republic of Dagestan (the Russian Federation) is presented, it includes 125 species and 2 subspecies. Three new aphid species are described here: Aphis dagestanica sp. nov. based on apterous viviparous females, oviparous females and apterous male, living on Caucasalia parviflora (Asteraceae), Aphis epilobiphaga sp. nov. based on apterous viviparous females, living on Epilobium colchicum (Onagraceae) and Aphis oxalicola sp. nov. based on apterous viviparous females, living on Oxalis stricta (Oxalydaceae). Redescription of Macrosiphum pulcherimum Nevsky, 1928 based on apterous viviparous females are given, a lectotype is designated and data provided on the distribution and biology of this species. Previously unknown males and oviparous females of Aphis leontodontis (Börner, 1950) and Brachyunguis zygophylli (Nevsky, 1928) and oviparous females of Aphis apocynicola Holman, 1992, are described. Notes about the distribution and biology of aphids recorded in Dagestan and on the completeness of the list are given.